Aspen Plus® simulation and techno-economic analysis of condensation and fractional distillation of plastic waste pyrolysis oil for sustainable aviation fuel production - Hanekom, Nicol Jesse (Stellenbosh : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.